2016
DOI: 10.29262/ram.v63i2.146
|View full text |Cite
|
Sign up to set email alerts
|

Conceptos básicos de las inmunodeficiencias primarias

Abstract: ResumenLas inmunodeficiencias primarias son un grupo heterogéneo de trastornos hereditarios ocasionados por defectos del desarrollo o función del sistema inmunológico, la mayoría se manifiestan a edad temprana por infecciones, datos de malignidad o por disregulación en la respuesta inmune, ya sea autoinflamación, autoinmunidad o alergia. Debido a que las inmunodeficiencias primarias son trastornos genéticos, la mayoría se heredan de forma autosómica recesiva. Las inmunodeficiencias primarias son más prevalente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
(5 reference statements)
1
1
0
4
Order By: Relevance
“…The clinical presentation is highly variable, but most present as recurrent infections, which are common in childhood and therefore may go unnoticed in the primary care setting. 1,2,18 We found that the most frequent group according to the IUIS 2015 classification was predominantly antibody deficiency, which is consistent with the international literature, 1,9 followed by CID with associated or syndromic features and then immunodeficiencies affecting cellular and humoral immunity. LASID announced that it had a registry of 8383 patients with innate errors of the immune system by August 2020, of which 53.2% had a predominantly antibody deficiency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The clinical presentation is highly variable, but most present as recurrent infections, which are common in childhood and therefore may go unnoticed in the primary care setting. 1,2,18 We found that the most frequent group according to the IUIS 2015 classification was predominantly antibody deficiency, which is consistent with the international literature, 1,9 followed by CID with associated or syndromic features and then immunodeficiencies affecting cellular and humoral immunity. LASID announced that it had a registry of 8383 patients with innate errors of the immune system by August 2020, of which 53.2% had a predominantly antibody deficiency.…”
Section: Discussionsupporting
confidence: 89%
“…Most of them present at an early age as recurrent or severe infections, malignancy, or dysregulation in the immune response; autoinflammation; autoimmunity; or allergic disease. 1,2 In 1970, the World Health Organization created a committee to classify these pathologies. 3 Subsequently, in 2015, the International Union of Immunological Societies Expert Committee for Primary Immunodeficiency (IUIS) modified the classification, given the recent advances of the last 40 years, with the aim to increase awareness, facilitate recognition, standardize nomenclature, standardize the approach, and promote optimal and early treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de los 10 grupos que la componen, están los defectos de la fagocitosis clasificados tanto en número como en función. 4,5 La enfermedad granulomatosa crónica (EGC) se clasifica como un EII funcional de la fagocitosis. Se transmite con dos patrones de herencia, ligado al X y autosómica recesiva.…”
Section: Generalidadesunclassified
“…Las inmunodeficiencias primarias (IDP) son trastornos hereditarios heterogéneos ocasionados por defectos del desarrollo o función del sistema inmunológico. 1 El comité de expertos de IDP de la Unión Internacional de Sociedades de Inmunología, en junio de 2017 propuso una clasificación por grupos que facilita las investigaciones clínicas y los estudios comparativos; 50 % de las IDP corresponden al grupo III: deficiencia predominantemente de anticuerpos. 2,3,4,5 Las inmunodeficiencias humorales sintomáticas más frecuentes en pacientes adultos son la inmunodeficiencia común variable (IDCV), la agammaglobulinemia ligada al cromosoma X y la deficiencia de subclases de inmunoglobulina G (IgG).…”
Section: Antecedentesunclassified